2016
DOI: 10.3892/ijmm.2016.2492
|View full text |Cite
|
Sign up to set email alerts
|

miR-409-3p sensitizes colon cancer cells to oxaliplatin by inhibiting Beclin-1-mediated autophagy

Abstract: The chemoresistance of colon cancer cells limits the efficacy of chemotherapy. miR-409-3p has been shown to be downregulated in various types of cancer. In the present study, we examined the role of miR-409-3p in colon cancer as well as the effects of miR‑409-3p on the sensitivity of colon cancer cells to oxaliplatin. The expression of miR-409 was significantly downregulated in the human colon cancer cell lines compared with the normal colon epithelial cells. Importantly, the miR-409-3p expression levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 36 publications
1
60
0
Order By: Relevance
“…Furthermore, miR-425-5p ihnibition reversed oxaliplatin resistance both in HTC116-resistant cells lines and xenograft models by modulating the expression of PDCD10 (364). Tan et al observed a negative correlation between miR-409-3p and resistance to Oxaliplatin in CRC resistant cells (365). Moreover, as a putative miRNAs modulator, also long intergenic noncoding RNA (LINC00152), can be involved in chemosensitivity of Oxaliplatin in CRC.…”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 99%
“…Furthermore, miR-425-5p ihnibition reversed oxaliplatin resistance both in HTC116-resistant cells lines and xenograft models by modulating the expression of PDCD10 (364). Tan et al observed a negative correlation between miR-409-3p and resistance to Oxaliplatin in CRC resistant cells (365). Moreover, as a putative miRNAs modulator, also long intergenic noncoding RNA (LINC00152), can be involved in chemosensitivity of Oxaliplatin in CRC.…”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 99%
“…Beclin-1, a key autophagy gene, was predicted as the target of miR-409-3p. Overexpression of miR-409-3p inhibited cell autophagic activity and enhanced the sensitivity to oxaliplatin, which were abrogated by restoration of beclin-1, suggesting that miR-409-3p sensitized CRC to oxaliplatin by inhibiting beclin-1-mediated autophagy [63].…”
Section: Roles Of Mirnas In Oxaliplatin Resistancementioning
confidence: 99%
“…Beclin‐1 is a unique autophagy‐related protein that drives autophagosome formation, the inhibition of which suppresses cell proliferation, but increases apoptosis in CRC cells . It has been shown that miR‐409‐3p sensitizes colon cancer cells to oxaliplatin by targeting beclin‐1 and inhibition of autophagy . Furthermore, transforming growth factor‐β (TGF‐β) signaling plays an important role in autophagy, the activation of which is mediated by the Smads.…”
Section: Micrornas Cell Death and Oxaliplatin Resistancementioning
confidence: 99%